Strategi pengembangan kurikulum dan pembelajaran Pendidikan Agama Islam - Muzakki Muzakki; Sukino Sukino; Wahab Wahab (At Turots: Jurnal Pendidikan Islam, 2023)
The research entitled Curriculum Development and Learning Strategy for PAI was examined using the type of library research (Library Research). This research was conducted by conducting an in-depth analysis of various sources relevant to the issues to be discussed. The documentary technique used in this study aims to collect data by collecting representative library materials sourced from books, journals, e-books, or online. This study was conducted in order to improve the quality of Islamic Religious Education. The curriculum and development of Islamic education learning must be returned to its philosophical roots with consideration of the supporting and inhibiting factors for success. Factors that must be considered are curriculum content, curriculum implementation models, and curriculum evaluation. Furthermore, according to the needs of students, the world of work, and society. Furthermore, PAI teachers must be able to apply various principles, such as learning strategies and approaches, and use learning media in various ways.